New difference sequence spaces defined by Musielak-Orlicz function - Mursaleen, Mohammad; Sharma, Sunil K.; Syed Abdul Mohiuddine,; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
We introduce new sequence spaces by using Musielak-Orlicz function and a generalized -difference operator on -normed space. Some topological properties and inclusion relations are also examined.